An innovative gynecological HDR brachytherapy applicator system for treatment delivery and real-time verification. (March 2019) - Romanyukha, Anna; Carrara, Mauro; Mazzeo, Davide; Tenconi, Chiara; Al-Salmani, Tebarak; Poder, Joel; Cutajar, Dean; Fuduli, Iolanda; Petasecca, Marco; Bucci, Joseph; Cerrotta, Annamaria; Pappalardi, Brigida; et al.
Highlights: A prototype of a multichannel vaginal cylinder with embedded diodes was developed. The system was characterized to perform source tracking in HDR brachytherapy. After pre-calibration, one "simple" and ten clinical treatments were verified. The system showed sub-mm and sub-second accuracy. Abstract: The multichannel vaginal cylinder (MVC) applicator employed for gynecological high dose rate (HDR) brachytherapy increases dose delivery complexity, and thus makes the treatment more prone to errors. A quality assurance (QA) procedure tracking the source throughout dose delivery can detect dwell position and time errors in the multiple channels of the applicator. A new MVC system with integrated real time in vivo treatment delivery QA has been developed based on diodes embedded on the outer surface of the MVC. It has been pre-calibrated and verified using a non-clinical treatment plan with consecutive test positions and dwell times within each catheter, followed by the delivery of ten clinical plans of adjuvant vaginal cuff brachytherapy following hysterectomy for endometrial cancer. The non-clinical verification showed overall mean dwell position and time discrepancies between the nominal and measured treatment of −0.2 ± 0.5 mm and −0.1 ± 0.1 s (k = 1), respectively. The clinical plans showed mean positional discrepancies of 0.2 ± 0.4 and 0.0 ± 0.8 mm, for the central and peripheral catheters, respectively, and mean dwell time discrepancies of −0.1 ± 0.2 and −0.0 ± 0.1 s for central and peripheral catheters, respectively. The innovative prototype of the MVC system has shown the ability to track the source with sub-mm and sub-second accuracy, and demonstrated potential for its incorporation into the clinical routine.